1994
DOI: 10.4098/at.arch.94-31
|View full text |Cite
|
Sign up to set email alerts
|

Home range, habitat selection and activity of the red fox in a Mediterranean coastal ecotone

Abstract: Home range, habitat selection and activity of the red fox in a Mediterranean coastal ecotone Paolo CAVALLINI and Sandro LOVARI* Cavallini P. and Lovari S. 1994. Home range, habitat selection and activity of the red fox in a Mediterranean coastal ecotone. Acta theriol. 39: 279-287.Ranging behaviour and activity of five (2 females, 3 males) red foxes Vulpes vulpes (Linnaeus, 1758) in the Mediterranean coastal area of Maremma Natural Park (central Italy; an area of great habitat diversity) are described. One f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…In comparison, post-epizootic foxes selected habitats with very dense vegetative cover, in agreement with work carried out on rural fox populations (Cavallini andLovari 1994, Lucherini et al 1995). Post-epizootic foxes significantly preferred to rest within allotment/woodland, with back gardens and grassland/scrub ranking equally in second place.…”
Section: Discussionsupporting
confidence: 75%
“…In comparison, post-epizootic foxes selected habitats with very dense vegetative cover, in agreement with work carried out on rural fox populations (Cavallini andLovari 1994, Lucherini et al 1995). Post-epizootic foxes significantly preferred to rest within allotment/woodland, with back gardens and grassland/scrub ranking equally in second place.…”
Section: Discussionsupporting
confidence: 75%
“…The red fox is widespread in all our study area, using both wood and open habitats (Cavallini and Lovari 1994). Its diet includes mainly juniper berries and insects while large mammals are used mainly during the cold season (Cavallini and Lovari 1994). A recent study confirmed a small use of roe deer during their fawning season: roe deer hairs were present in only two scats out of 205 (Coneybeer 2003).…”
Section: Study Areamentioning
confidence: 82%
“…No study has been published on the local diet of the wolf, but preliminary observations suggest that the fallow deer appears to be the most used prey (Manghi et al 2006). The red fox is widespread in all our study area, using both wood and open habitats (Cavallini and Lovari 1994). Its diet includes mainly juniper berries and insects while large mammals are used mainly during the cold season (Cavallini and Lovari 1994).…”
Section: Study Areamentioning
confidence: 98%
“…But for foxes as a species, no clear conclusions regarding habitat preferences within the home range in autumn could be drawn due to insuffi cient data. In heterogeneous areas, where a number of resources are available at the same time in different habitats, foxes selected a diversity of habitats rather than any one in particular (Cavallini & Lovari 1994. This might be true also in our study area.…”
Section: Habitat Selection and Use Of Individual Speciesmentioning
confidence: 87%